Rancang Bangun Sistem Informasi Penjadwalan Produksi Menggunakan Aturan Prioritas Pada PT. IGLAS (Persero) - Gilang Ramdhan; Henry Bambang Setyawan; Tony Soebijono (Jurnal Sistem Informasi Universitas Dinamika, 2015)
PT. IGLAS (Persero) is a manufacturing company of glass packaging (bottles). The company currently often late in a customer demand fulfillment. This problem due to several factors such as conventional way of schedulling and inneficient production process. Based on these problems, it would require a production scheduling information system using the priority rules to solve. This information system can provide production schedule more effectively according to choosen criteria from five methods that have been used. The criterias used are average processing time, utilization, average number of jobs in the system, and average number of delayed jobs. Meanwhile five methods used are, First Come First Serve (FCFS), Earliest Due Date (EDD), Shortest Processing Time (SPT), Longest Processing Time (LPT), dan Critical Ratio (CR). Based on the information system created and series of trials performed, company has a more effective queued schedule in accordance with desired company criterias, so that all of customer demand can be fulfilled and timely completion.